2021
DOI: 10.4314/sajas.v51i2.4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oregano essential oil and capsicum extract on fattening, serum constituents, and rumen fermentation of lambs

Abstract: This study investigated dietary supplementation of weaned lambs with Origanum vulgare essential oil and Capsicum oleoresin (chilli pepper) extract. Thirty-six eight-week-old male and female Menemen lambs were used in this study. Three dietary treatment groups consisted of T1, an unsupplemented control group; T2, a group supplemented with 300 mg/kg oregano essential oil, and T3, a group supplemented with 300 mg/kg Capsicum oleoresin. Feed and fresh water were available to the lambs ad libitum during the 56-day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
2
0
1
Order By: Relevance
“…The results obtained in the present study are consistent with previous research [13,40,41] in sheep fed with diets and different levels of OEO (Oreganun vulgare L.). However, they differ from what was reported by Ünlu et al [28] and Passetti et al [12]. Generally, the ruminal concentration of NH 3 -N is in the range 10 to 50 mg dL −1 [13]; the results obtained in the present study are within the range recommended by Hoover [42] for the initiation of microbial growth and to maximize microbial protein synthesis in sheep [43], and coincide with the research carried out by Jiao et al [13] and Passetti et al [12].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The results obtained in the present study are consistent with previous research [13,40,41] in sheep fed with diets and different levels of OEO (Oreganun vulgare L.). However, they differ from what was reported by Ünlu et al [28] and Passetti et al [12]. Generally, the ruminal concentration of NH 3 -N is in the range 10 to 50 mg dL −1 [13]; the results obtained in the present study are within the range recommended by Hoover [42] for the initiation of microbial growth and to maximize microbial protein synthesis in sheep [43], and coincide with the research carried out by Jiao et al [13] and Passetti et al [12].…”
Section: Discussioncontrasting
confidence: 99%
“…Essential oils improve the taste and palatability of feed, thus increasing voluntary intake, resulting in better weight gain [1]. In the present investigation, no effect on final weight, DMI, DWG, and FCR was observed; the results obtained are similar to those reported by Ünal and Kocaba ǧli [15] and Ünlü et al [28] when including different levels of OEO in diets for sheep. Other similar results were reported by Farghaly and Abdullah [16], who included 2.5% OEO in the diets of Saidi sheep.…”
Section: Discussionsupporting
confidence: 90%
“…[ 16 ]. The current findings also back up the findings of [ 45 ], who reported that dietary supplements had no influence on serum creatinine concentration. Elevated concentrations of creatinine suggest insufficient protein and amino acid metabolism, which can lead to kidney damage and a coronary artery disease [ 46 ].…”
Section: Discussionsupporting
confidence: 89%
“…Essential oils (EOs) extracted from plants using different methods have been used as feed additive alternatives to antibiotics for stabilizing rumen flora in recent years. Much research has described the effects of various EOs and their active components (secondary metabolites) on the microorganisms that live in the rumen, as well as the metabolic processes that take place in the rumen (McIntosh et al, 2003;Benchaar et al, 2007;Kekana et al, 2021;Ünlü et al, 2021). Most of these studies are regarding rumen bacteria and rumen fermentation.…”
Section: Introductionmentioning
confidence: 99%